IMPLEMENTATION OF EMPLOYEE EMPOWERMENT AT GILANG RAMADHAN STUDIO BAND MUSIC SCHOOL (KAWANGKOAN BRANCH) - Sambouw, Agnes F. O.; Mangantar, Maryam; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The final project aims to find out the implementation of employee empowerment at Gilang Ramadhan Studio Band Music School Kawangkoan Branch. By using Khan's theory, which contains several indicators, namely Desire, Trust, Confidence, Credibility, Accountability, Communication. The research method used is a qualitative method. The analysis technique uses observation, interviews, and documentation. The results of the study found that desire on GRSB Kawangkoan has been well empowered, trust in GRSB Kawangkoan can be said to be enough empowered, confident employees at GRSB Kawangkoan have been well empowered, confident employees at GRSB Kawangkoan have been well empowered, credibility in GRSB Kawangkoan has been well empowered, accountability at GRSB Kawangkoan is quite well empowered, communication in GRSB Kawangkoan has been well empowered.Â Keywords: Empowerment, performance, employee